Komponen-komponen Administrasi Personalia Guru dan Tantangan di Era Digital: Solusi Menghadapi Perubahan Zaman - Fatimah, Meti; Winarno, Dwi; Kurniawati, Wakhidah (Lembaga Yasin AlSys, 2024)
Teacher personnel administration is an important aspect in the effective management of educational staff in the school environment. This article aims to explore what teacher personnel administration is, the challenges in the current era and its solutions through a literature study approach. Personnel administration covers various aspects, such as recruitment, selection, development, performance assessment, promotion, and teacher welfare. Based on the literature review, the role of good teacher personnel administration is crucial to improving the quality of education. Proper management of teacher personnel can improve their motivation, performance, and welfare, thus having a positive impact on the teaching and learning process. This study also highlights the challenges in teacher personnel administration at various levels of education, especially related to government policies and school management. In conclusion, the implementation of effective teacher personnel administration plays an important role in creating a quality and sustainable education system.